Investigation and Development of Quality of Service Management for Web based Services: Managing Quality of Service from the End-User Perspective - Dalton, Eamonn (Trinity College Dublin. Department of Computer Science, 2000)
With the advent of Web based delivery of business applications and increasing dependency on these services, management of availability and performance are critical. For service providers to offer guarantees on Web based application performance of services delivered via Hypertext Transfer Protocol (HTTP), they must implement Quality of Service (QoS) and have a composite view of service quality across all the components in the service delivery chain including databases, networks and webservers. In most cases this is not possible as different parts of the infrastructure are outsourced to different service providers or managed by the customer. Even with all this information available it is still extremely difficult to diagnose how service performance is perceived by the end user. This dissertation describes the design and implementation of a framework that supports the monitoring of Web delivered services from the end-users perspective. The service performance and availability can then be compared against a Service Level Agreement. The framework consists of a number of components. These include a local proxy on the end user?s host that intercepts HTTP requests and replies. This allows the monitoring of availability and performance parameters as perceived by the end user. The framework also involved the design of a SLA template specifically for Web delivered services that can map these parameters captured by the proxy in a meaningful way so that it is possible to specify how a service delivered over HTTP should perform from the end-user perspective. The proxy encompasses a number of features including automatic retrieval of a Service Level Agreement (SLA) with a server. Finally an application was developed that demonstrated how the framework can be applied to monitor SLA compliance for a Web delivered service.
Keywords: Computer Science